Pengembangan Buku Teks Peradaban Alat Komunikasi Berbasis PjBL untuk Menumbuhkan Karakter Berwawasan Luas - Vania Ulima Magfiroh; Gregorius Ari Nugrahanta (Educatio, 2025)
This study successfully developed a communication civilization textbook based on Project Based Learning (PjBL) using a genetic approach through the five stages of the ADDIE model. The product was validated by experts with an average score of 3,94 in the “very good” category, indicating that it is suitable for use without revision. The textbook includes five creative projects relevant to the theme of communication civilization and is designed to foster broad-minded character. The effectiveness test showed that the developed textbook had a significant impact on improving elementary students’ broad-minded character. The Mann-Whitney test (U = 11,500; p < 0.001) revealed a significant difference between the control and experimental groups, with a large effect size (r = 0,83). The N-gain test demonstrated high effectiveness in the experimental group (71,89%) compared to the control group (30,83%). The z-score analysis confirmed these findings, with an average z-score of 0.85 in the experimental group, indicating scores well above the mean, while the control group tended to remain at negative scores (-0,85). Furthermore, the interrater reliability test using Krippendorff’s alpha produced an average α = 0,779 in the “high” category, confirming strong consistency among raters. Thus, the development of this PjBL-based textbook is proven to be feasible, effective, and reliable as both a learning medium and a means of strengthening broad-minded character in elementary school students.